Culture and Enaction. An approach from a Lexical Study of the Spanish Online Press (Signifiances (Signifying), 2024)
In this paper we will pay attention to the convergence of enaction and culture in human lexicon. To that end, we will carry out an analysis of real interactions of a special type of computer-mediated communication (CMC), i.e., the comment’s sections of several Spanish digital newspapers. Our aim is to explain how both an enactive and cultural analysis of our corpus, based on authentic readers’ comments, lead to a more comprehensive explanation of the cognitive and thematically related networks from a discursive point of view. Dans cet article, nous prêterons attention à la convergence de l’énaction et de la culture dans le lexique humain. Pour cela, nous effectuerons une analyse des interactions réelles d’un type particulier de communication médiée par ordinateur (CMO), à savoir les sections de commentaires de plusieurs journaux espagnols en ligne. Notre objectif est d’expliquer comment une analyse à la fois énactive et culturelle de notre corpus, basée sur les commentaires authentiques de lecteurs, conduit à une explication plus complète des réseaux cognitifs et thématiques liés d’un point de vue discursif.